Waqf as a driven source for human capital development: a comparative analysis of Bangladesh and Malaysia - Taifur, Mahfuzul Alam; Ab Rahman, Asmak (Universiti Teknologi MARA Selangor, 2025)
This article explores the significant role of waqf in the development of human capital, focusing on Bangladesh and Malaysia. The aim of this study is to outline the importance of human capital in economic development and how waqf can be utilised to foster education, training, and skills, contributing to overall societal welfare and prosperity. It presents a qualitative research approach, employing interviews and thematic analysis to explore the effectiveness and challenges of waqf in human capital development. The study reviews theoretical underpinnings of human capital from both Western and Muslim scholars and compares the practical applications and outcomes of waqf-funded initiatives in enhancing human capital in the two countries. The findings illustrate varied perspectives and implementations in Bangladesh and Malaysia, influenced by cultural, economic, and institutional factors. The article concludes by suggesting that waqf can significantly contribute to human capital development, with implications for policy and practice in Muslim-majority countries facing similar challenges. This study uniquely examines the role of waqf in human capital development in Bangladesh and Malaysia, integrating both Western and Islamic perspectives. By comparing waqf-funded initiatives across these distinct cultural and economic contexts, it identifies key challenges and opportunities that shape effective outcomes. The findings provide valuable insights for policymakers and practitioners, suggesting ways to leverage waqf for human capital enhancement in Muslim-majority countries with similar socio-economic goals.